2017
DOI: 10.18632/oncotarget.20702
|View full text |Cite
|
Sign up to set email alerts
|

BMAL1 facilitates trophoblast migration and invasion via SP1-DNMT1/DAB2IP pathway in recurrent spontaneous abortion

Abstract: The underlying mechanism about rhythms and epigenetics leading to aberrant trophoblast migration and invasion in recurrent spontaneous abortion (RSA) remains unknown. Brain and muscle ARNT-like protein 1 (BMAL1) is considered as a crucial role in fertility, and polymorphism of BMAL1 gene has been reported to be associated with risk of miscarriage. However, the functional role of BMAL1 in RSA is not fully understood. Previous study shows the descended expression of DNA 5′-cytosine-methyltransferases 1 (DNMT1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…On the other hand, it has been reported that Bmal1 inhibits invasion in tongue squamous cell carcinoma cells and telomerase reverse transcriptase gene ( hTERT ) mediates Bmal1-driven sensitivity to an antineoplastic agent paclitaxel 44 . BMAL1 also promoted migration and invasion in an immortalized human extravillous trophoblast cell line HTR-8/SVneo 49 . In the present study, we used an invasive breast cancer cell line, MDA-MB-231, to analyse the effect of BMAL1 mutation on invasion.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, it has been reported that Bmal1 inhibits invasion in tongue squamous cell carcinoma cells and telomerase reverse transcriptase gene ( hTERT ) mediates Bmal1-driven sensitivity to an antineoplastic agent paclitaxel 44 . BMAL1 also promoted migration and invasion in an immortalized human extravillous trophoblast cell line HTR-8/SVneo 49 . In the present study, we used an invasive breast cancer cell line, MDA-MB-231, to analyse the effect of BMAL1 mutation on invasion.…”
Section: Discussionmentioning
confidence: 94%
“…Many of the genes that we identified as targets of these miRNA are believed to play a role in the preparation and development of the uterus in early pregnancy (TWIST1 [130], CDK6 [95], RUNX1 [138], CDK6 [95], MITF [130], HNRNPA2B1 [118] and BMP2 [123]), decidualisation (CDKN1A [153] and STAT3 [150]), implantation of the embryo (RECK [134], KRAS [122], CDH1 [155] and SMAD4 [160]) and the activation of the migration, invasion, proliferation and differentiation of the trophoblast (MAPK1 [125], MYC [135], TGFB [141], DAB2IP [103], RECK [133], SMAD7 [88] and STAT3 [149]). They continue to play roles during pregnancy…”
Section: Comparison Of Umbilical Cord Plasma Mirna Profiles To Adult mentioning
confidence: 99%
“…While CCNG2 [96] and FOXO4 [156] are downregulated in the placenta at full term. A number of these genes have been implicated in complications of preganacy including: miscarriage (VEGFA [147], DAB21P [103], CDKN1A [151,151,152], PTEN [124] and MDM2 [128]); preeclampsia (CD1C [105], CYP19A1 [102], VEGFA [147], CDKN1C [100,101], DAB2IP [104], CCNG2 [111] and GRB2 [116]); pre-term labour (RhoA [142,143]); gestational diabetes (CCNG2 [111,112], ITGA6 [113], RAB23 [113] and FOXO4 [158]); gestational trophoblastic disease (MDM2 [127]); male-specific neonatal encephalopathy (MECP2 [132]), neural tube defects (ITGA6 [113] and RAB23 [113]); Carpenter Syndrome (RAB23 [129]); intrahepatic cholestasis of pregnancy (PUM1 [139]); ectopic pregnancies (DKK3 [106]); and foetal conotruncal anomalies (MAPK1 [126].…”
Section: Rbmxl1mentioning
confidence: 99%
“…Indeed, it has been shown that trophoblast dysfunction, due to compromised trophoblast infiltration and apoptosis, as well as multiple aberrant signal transduction pathways (64), could lead to adverse pregnancy outcomes, including uRPL (65). In detail, all the impaired pathways previously investigated in RPL trophoblast cells functions (including kisspeptin/GPR54 and PIBF/PR pathways, C4d and Bb, MBL, NOD1 and NOD2 via MAPK/p38 pathway, miR-27a-3p/USP25 axis, Fas and FasL, PKC protein, CCNA2, TWIST, Prototype and Chimera-Type Galectins, miR-520 and PARP1, BMAL1 via SP1-DNMT1/DAB2IP pathway, EIF5A1 via ARAF-mediated activation of integrin/ERK signaling pathway, Stathmin-1, peroxiredoxin2are) are linked to trophoblast migration, proliferation, invasion and apoptosis processes potentially relevant for RPL pathogenesis (64,(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78). Less is known about potential immunological impaired processes induced by trophoblast dysfunction.…”
Section: The Fetal-maternal Interfacementioning
confidence: 99%